Incomes and employment of Italian women, 1900-1950 - Giacomo Gabbuti; María Gómez León (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2023)
In this paper, we aim to address a major gap in the economic history of interwar Italy, by discussing the evolution of women's incomes and employment during this crucial period of Italian and European history. After examining the available statistical evidence, we build on recently reconstructed dynamic social tables for Italy, from 1900 to 1950, to chart trends in both gender wage gap and female labour force participation, disaggregated by major sectors. Our methodology greatly contributes to the understanding of history of women's work for pay, placing it within the broader dynamics of income inequality. This approach also allows us to shed light on the growing gap between Fascist claims and the reality of women's work: despite discriminatory laws, throughout these decades women increased their presence and visibility in all sectors, with the only exception of agriculture. Conversely, the March on Rome marked the beginning of a strong reversal in terms of gender wage gaps. We are thus able to confirm the important role played by female work in the Fascist accumulation model, characterized by wage squeezes and reduced private consumption.
Keywords: E24; J16; J21; J31; N34; 330; Fascist Italy; female labour force participation; wage gaps; dynamic social tables